Management of older adults after mild head trauma in an oral and maxillofacial surgery clinic - Sakkas, Andreas; Weiß, Christel; Scheurer, Mario; Pietzka, Sebastian; Wilde, Frank; Mohammad, Qasim; Thiele, Oliver Christian; Mischkowski, Robert Andreas; Ebeling, Marcel (European geriatric medicine, 2023)
To determine the intracranial pathologies and treatment outcome after mild traumatic brain injury (mTBI) in patients aged ≥65 years referred to a clinic for oral and maxillofacial surgery.
Online veröffentlicht: 19. April 2023
Gesehen am 24.07.2024